Teologi Digital dalam Pendidikan Kristen: Antara Kesetiaan Tradisi dan Relevansi Kontemporer - Berta Randabunga; Ibrahim Ibrahim (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2026)
This article examines the role of digital theology in Christian education by highlighting the tension between the demands of relevance in the digital age and fidelity to theological tradition. This study departs from the research gap that previous studies tended to be descriptive, i.e. only explaining the opportunities and challenges of digitalization without deeply analyzing the theological tension between tradition and digital transformation. This research aims to explore opportunities, challenges, and theological reflective frameworks in the integration of digital technology in Christian education to remain rooted in faith as well as contextual. The method used is a qualitative literature study by analyzing theological literature, Christian education, and current research on church digitization. The results of the study show that digital theology opens up opportunities such as expanding access to education, learning innovation, increasing student participation, and forming virtual faith communities. Nevertheless, fundamental tensions are found in the aspects of authority, presence, community, and faith formation. Theoretically, digital theology is understood as a critical reflective framework that negotiates Christian traditions and digital culture, while practically demanding a pedagogical approach that is critical, adaptive, and remains grounded in Scripture and church traditions. Artikel ini mengkaji peran teologi digital dalam pendidikan Kristen dengan menyoroti ketegangan antara tuntutan relevansi di era digital dan kesetiaan terhadap tradisi teologis. Kajian ini berangkat dari gap penelitian bahwa studi sebelumnya cenderung bersifat deskriptif, yaitu hanya memaparkan peluang dan tantangan digitalisasi tanpa menganalisis secara mendalam ketegangan teologis antara tradisi dan transformasi digital. Penelitian ini bertujuan mengeksplorasi peluang, tantangan, serta kerangka reflektif teologis dalam integrasi teknologi digital pada pendidikan Kristen agar tetap berakar pada iman sekaligus kontekstual. Metode yang digunakan adalah studi pustaka kualitatif dengan menganalisis literatur teologi, pendidikan Kristen, dan penelitian terkini tentang digitalisasi gereja. Hasil penelitian menunjukkan bahwa teologi digital membuka peluang seperti perluasan akses pendidikan, inovasi pembelajaran, peningkatan partisipasi peserta didik, serta pembentukan komunitas iman virtual. Namun demikian, ditemukan ketegangan mendasar pada aspek otoritas, kehadiran, komunitas, dan formasi iman. Secara teoretis, teologi digital dipahami sebagai kerangka reflektif kritis yang menegosiasikan tradisi Kristen dan budaya digital, sementara secara praktis menuntut pendekatan pedagogis yang kritis, adaptif, dan tetap berlandaskan Kitab Suci serta tradisi gereja.